2018
DOI: 10.5009/gnl17414
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcomes of Endoscopic Submucosal Dissection in Patients with Early Gastric Cancer: A Prospective Multicenter Cohort Study

Abstract: Background/AimsEndoscopic submucosal dissection (ESD) has been regarded as a curative treatment for early gastric cancer (EGC) in indicated cases. The aim of this study was to evaluate the nationwide long-term clinical outcomes of ESD for EGC in Korea.MethodsA prospective multicenter cohort study was performed to evaluate the long-term efficacy of ESD for EGC within pre-defined indications at 12 institutes in Korea. The cases that met the expanded criteria upon pathological review after ESD were followed for 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 15 publications
4
37
0
Order By: Relevance
“…ESD was developed to achieve en bloc resection of larger tumors in the stomach and has been accepted as standard treatment for early gastric cancer with minimal risk of lymph node metastasis [11,12]. Recent studies of the efficacy of ESD for the treatment of SNDA report high en bloc and complete resection rates of up to 80-100% [13][14][15][16], In this study, the en bloc anc complere resection rates were 90.0 and 80.0%, which is similar to the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…ESD was developed to achieve en bloc resection of larger tumors in the stomach and has been accepted as standard treatment for early gastric cancer with minimal risk of lymph node metastasis [11,12]. Recent studies of the efficacy of ESD for the treatment of SNDA report high en bloc and complete resection rates of up to 80-100% [13][14][15][16], In this study, the en bloc anc complere resection rates were 90.0 and 80.0%, which is similar to the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…49 A Korean multicenter prospective study published in 2018 reported the incidence of local recurrence to be 0.7% in patients who had curative ESD and 2.4% who had non-curative ESD. 188 Thus, since the incidence of local recurrence following curative ESD is below 1%, detecting synchronous or metachronous gastric cancer must be prioritized before detecting local recurrences. Since patients with early gastric cancer who receive endoscopic resection have most of their gastric mucosa intact, they are more prone to developing metachronous and synchronous gastric cancers compared with those after surgical gastrectomy.…”
Section: Statement G12: We Recommend Regular Surveillance Endoscopy Ementioning
confidence: 99%
“…Confirmatory data on the role of endoscopic submucosal dissection (ESD) in patients with early GC were published in the last year. In a Korean prospective multicenter study by Kim et al , 697 patients with early GC who met the absolute and extended criteria and underwent ESD were followed for 5 years. Only selected centers performing a minimum of 20 ESD per year took part to this study.…”
Section: Gastric Cancer: Treatmentmentioning
confidence: 99%